2021
DOI: 10.4236/jss.2021.96006
|View full text |Cite
|
Sign up to set email alerts
|

Research Status about Influence Factors of International Students’ Cross-Cultural Adaptation with Different Models

Abstract: With the advancement of global economic integration, the internationalization of higher education is constantly increasing, along with flourishing studies about cross-cultural adaptation of international students. Cross-cultural adaptation of international students was studied by researchers from different perspectives such as cross-cultural psychology, cross-cultural communication, and social psychology. To provide theoretical basis for the management of international students, this paper summarizes several p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
(49 reference statements)
1
5
0
4
Order By: Relevance
“…Cao and Meng (2019) concluded, on the basis of the results of their experiential research, that English language proficiency will have both direct and indirect effects on students’ psychological and social adjustment (Bethel et al, 2020). This is also consistent with the results presented by Luo and Zhang (2021). Researchers found that students’ English language proficiency positively correlated with their intercultural psychological, sociocultural and academic adjustment in a multicultural environment.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Cao and Meng (2019) concluded, on the basis of the results of their experiential research, that English language proficiency will have both direct and indirect effects on students’ psychological and social adjustment (Bethel et al, 2020). This is also consistent with the results presented by Luo and Zhang (2021). Researchers found that students’ English language proficiency positively correlated with their intercultural psychological, sociocultural and academic adjustment in a multicultural environment.…”
Section: Discussionsupporting
confidence: 94%
“…A recent study of 263 international students at a South African university found that motivation, cultural intelligence and sociocultural adjustment were predictive factors of academic performance (Mokhothu & Callaghan, 2018). Lack of acculturation can not only lead to academic failure (Credé & Niehorster, 2012) but can also cause serious physical and psychological illnesses (Luo & Zhang, 2021; Smith & Khawaja, 2011; Yu et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The diversity of the world's languages, cultures, religions, beliefs and traditions manifests the most in the languages. Cross-cultural communication is a currently thriving field as globalisation, instant communication and easy travel access make people from different parts of the world more connected than they have ever been in the past centuries (Bakhov et al, 2021;Luo & Zhang, 2021;Shadiev et al, 2021). Alongside the significant, positive interest people generally have when it comes to learning and interacting with people from different cultures, this diversity is also a causal factor in cross-cultural misunderstandings when communicating (Herdi & Handayani, 2020;Sahadevan & Sumangala, 2021).…”
Section: Introductionmentioning
confidence: 99%